Interactive 3D visualization for tropical plant species - Chang, Siow Wee (2019)
Augmented Reality (AR) is gaining more popularity nowadays as AR enables the user to see, hear and feel the virtual elements in the real world. The advancement in AR has made an impressive remark in the field of game, education, tourism, exploration, and advertising. In this research, an interactive 3D visualization for tropical plant species is developed. It provides the user with better visualization of plant species through AR. It permits the user to view three-dimensional rotatable models through a marker in a book, on a pamphlet or on signage. It enables the user to have a better idea of how the plants would look like in real life rather than plain two-dimensional images. In order to track the 3D models, markers or image targets are developed to track various 3D plant models. The AR markers developed are rich in detail, good contrast and with no repetitive patterns to have the good tacking ability. This research consists of five main stages which are image acquisition, 3D model construction, marker design, integration of 3D model into marker, and graphical user interface (GUI) design. This application permits the user to access the 3D models of the topical plant species with the availability of the marker anywhere and anytime. In addition, it is portable and low-cost interactive learning material for school children as well as the public.